2020
DOI: 10.3390/e22060639
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on the Transmit Power of b-Modulated NFDM Systems in Anomalous Dispersion Fiber

Abstract: The performance of various nonlinear frequency division multiplexed (NFDM) fiber-optic transmission systems has been observed to decrease with increasing signal duration. For a class of NFDM systems known as b-modulators, we show that the nonlinear bandwidth, signal duration, and power are coupled when singularities in the nonlinear spectrum are avoided. When the nonlinear bandwidth is fixed, the coupling results in an upper bound on the transmit power that decreases with increasing signal duration. Signal-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…If needed, we then can use both computed quantities to find the reflection coefficient (10). We note that within the b-modulation concept, which has turned out to be the most efficacious NFDM method developed so far, we utilise the b(ξ ) functions as information carriers [24][25][26][27] .…”
Section: Nf Spectrum Associated With Finite-extent Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…If needed, we then can use both computed quantities to find the reflection coefficient (10). We note that within the b-modulation concept, which has turned out to be the most efficacious NFDM method developed so far, we utilise the b(ξ ) functions as information carriers [24][25][26][27] .…”
Section: Nf Spectrum Associated With Finite-extent Signalsmentioning
confidence: 99%
“…In our current study we specifically address the continuous NF spectrum: our goal is to compute the profile r(ξ ) given the localised q(t) shape. Then, we mention that the continuous NF spectrum modulation using the special technique coined b-modulation [24][25][26][27] has provided the highest NFDM data rates so far 12,28 . Thus, in this paper we also address the recovery of the b-coefficient, b(ξ ) ∈ C, ξ ∈ R, given q(t).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the power of the signal is severely limited when using b-modulation, since |b(λ)| < 1 must hold for any λ ∈ R [17,31]. Theoretical bounds on the power in b-modulated systems (and for continuous spectrum modulation in the normal dispersion regime) have been recently given [34].…”
Section: The B-modulationmentioning
confidence: 99%
“…At higher powers, solitons carry most of the energy and the dispersive part plays a minor role [10]- [12]. On the other hand, it was found that the energy contained in a directly modulated dispersive part can be bounded [13].…”
Section: Introductionmentioning
confidence: 99%